2016
DOI: 10.1021/acs.inorgchem.6b01030
|View full text |Cite
|
Sign up to set email alerts
|

Gallium(III)-Containing, Sandwich-Type Heteropolytungstates: Synthesis, Solution Characterization, and Hydrolytic Studies toward Phosphoester and Phosphoanhydride Bond Cleavage

Abstract: The gallium(III)-containing heteropolytungstates [Ga4(H2O)10(β-XW9O33)2](6-) (X = As(III), 1; Sb(III), 2) were synthesized in aqueous acidic medium by reaction of Ga(3+) ions with the trilacunary, lone-pair-containing [XW9O33](9-). Polyanions 1 and 2 are isostructural and crystallized as the hydrated sodium salts Na6[Ga4(H2O)10(β-AsW9O33)2]·28H2O (Na-1) and Na6[Ga4(H2O)10(β-SbW9O33)2]·30H2O (Na-2) in the monoclinic space group P21/c, with unit cell parameters a = 16.0218(12) Å, b = 15.2044(10) Å, c = 20.0821(1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 98 publications
0
24
0
Order By: Relevance
“…The stability of molecular WOCs is a topic of current interest due to the possibility of the WOCs to decompose into catalytically active oxide nanoparticles [22] . Note that 183 W or 31 P NMR measurements on Co 4 , Co 9 and Co 20 could not be performed, due to the low solubility and strong paramagnetic nature of the incorporated Co II metal centers [23] . Hence, various reloading experiments and post‐catalytic characterizations were conducted to demonstrate that O 2 evolution is indeed triggered by the investigated Co‐GT and to verify their integrity under turnover conditions [24]…”
Section: Resultsmentioning
confidence: 99%
“…The stability of molecular WOCs is a topic of current interest due to the possibility of the WOCs to decompose into catalytically active oxide nanoparticles [22] . Note that 183 W or 31 P NMR measurements on Co 4 , Co 9 and Co 20 could not be performed, due to the low solubility and strong paramagnetic nature of the incorporated Co II metal centers [23] . Hence, various reloading experiments and post‐catalytic characterizations were conducted to demonstrate that O 2 evolution is indeed triggered by the investigated Co‐GT and to verify their integrity under turnover conditions [24]…”
Section: Resultsmentioning
confidence: 99%
“…The high Lewis acidity of Zr(IV)-POMs makes them also interesting as catalysts for the hydrolysis of the extremely stable phosphoester and peptide bonds, which are found in DNA and proteins, respectively. Our previous work has shown that Zr(IV) substituted Wells-Dawson [[Zr(α 2 -P 2 W 17 O 61 ) 2 ] 16− , Zr1-WD2 (Vanhaecht et al, 2013), and [Zr 4 (α 2 -P 2 W 16 O 59 ) 2 (μ 3 -O) 2 (OH) 2 (H 2 O) 4 ] 14− POMs (Luong et al, 2016a), as well as Keggin POMs [(Et 2 NH 2 ) 8 [{α-PW 11 O 39 Zr(μ-OH)(H 2 O)} 2 ] and (Et 2 NH 2 ) 10 [(α-PW 11 O 39 ) 2 Zr] (Luong et al, 2014, 2015a,b, 2016b, 2017)], efficiently catalyze the cleavage of phosphoester bonds in nucleic acids as model substrates (Vanhaecht et al, 2013; Luong et al, 2014, 2015a,b, 2016a,b,c; Kandasamy et al, 2016). Also the selective cleavage of double-stranded DNA has been demonstrated (Luong et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, to prove stability of [Ce(H 2 O) 3 (GeW 10 ) 2 ] 9– and [Zr(H 2 O) 3 (GeW 10 ) 2 ] 8– indirectly, the IR spectra of the polyanions were recorded after precipitation with tetrabutylammonium bromide, thereby clearly showing the characteristic W–O–W bridging and terminal W=O vibrations in the tungsten fingerprint area from 300–1000 cm –1 , which proves the solution stability of the polyanions after reaction with NPP ( Figures S2, S3 ) and DMNP, respectively ( Figure S4 ), and represents an established method frequently used in POM chemistry. 39 Subsequent control experiments with CeCl 3 and ZrOCl 2 as nonshielded free Lewis metal centers resulted in the formation of precipitates or insoluble Zr(IV) hydroxyl polymeric gels, respectively, shown by the disappearance of the 1 H NMR peaks even at low concentrations of the corresponding metal center, which additionally proves the solution stability of the POM compounds under reaction conditions ( Figure S14 ). 40 42 The recyclability of [Zr(H 2 O) 3 (GeW 10 ) 2 ] 8– as a catalyst for the decontamination of DMNP was tested in a consecutive experiment by reloading the reaction mixture with DMNP substrate after 31 P NMR measurements confirmed that 97% of DMNP was converted to the hydrolysis product DMP ( Figure S19 ).…”
Section: Resultsmentioning
confidence: 84%
“…Solution stability studies on [Ce(H 2 O) 3 (GeW 10 ) 2 ] 9– and [Zr(H 2 O) 3 (GeW 10 ) 2 ] 8– after reaction with NPP and DMNP were intended to be performed; however, due to the low solubility and sensitivity of the 183 W nucleus (14.3% natural abundance), the 183 W NMR measurements at conditions pertinent to the catalytic reactions were not very informative, which is a common problem encountered in POM chemistry. 39 Considering the low solubility of the polyanion, the POM concentrations used for the hydrolysis experiments were too low to obtain reasonable amounts for consecutive postcatalytic PXRD measurements. Hence, to prove stability of [Ce(H 2 O) 3 (GeW 10 ) 2 ] 9– and [Zr(H 2 O) 3 (GeW 10 ) 2 ] 8– indirectly, the IR spectra of the polyanions were recorded after precipitation with tetrabutylammonium bromide, thereby clearly showing the characteristic W–O–W bridging and terminal W=O vibrations in the tungsten fingerprint area from 300–1000 cm –1 , which proves the solution stability of the polyanions after reaction with NPP ( Figures S2, S3 ) and DMNP, respectively ( Figure S4 ), and represents an established method frequently used in POM chemistry.…”
Section: Resultsmentioning
confidence: 99%